Work Stress and Health in a Globalized Economy [electronic resource] : The Model of Effort-Reward Imbalance - Siegrist, Johannes; Wahrendorf, Morten; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2016)
This book provides a comprehensive, updated summary of research evidence on the effects of stressful working and employment conditions on workers? health, as based on one of the worldwide leading theoretical models, effort-reward imbalance. It offers three innovative features that are appealing for research as well as for policy. Firstly, it presents and discusses comparable research findings from different continents, in particular from Japan, China, and Latin America. Secondly, it extends the conceptual framework of research on this topic by analysing associations of work stress with health in a life course perspective, and by linking these associations to the macro-level of national labour and social policies. Thirdly, the book helps to strengthen programs and policies that aim at promoting healthy work locally, nationally, and internationally, by providing solid facts on which such programs can be based.
Keywords: Psychology; Medical research; Health economics; Medical economics; Quality of life; Health Psychology; Industrial Psychology; Psychology; Industrial, Organisational and Economic Psychology; Health Psychology; Health Economics; Quality of Life Research